Effects of K, Rb, and Br doping on Cs3Bi2I9 perovskites: A design of experiments approach - Medeiros, Rodolfo L.B.A.; Melo, Dulce M.A.; Oliveira, Ângelo A.S.; Macedo, Heloísa P.; Fabris, Guilherme S.L.; Sambrano, Julio R. [UNESP]; Maziviero, Fernando V.; Braga, Renata M.; Morgado, Edisson (Elsevier, 2024)
This work presents the effect of doping with different species on the structural sites of lead-free halide perovskites, aiming to evaluate the potential of the produced materials as photoabsorbing layers in 3rd generation solar cells. Lead-free perovskite films of Cs3Sb2I9, CsCu2I3, Cs3Bi2I9, and CsPbI3 were synthesized via the spin-coating method and characterized using X-ray diffraction, scanning electron microscopy with chemical microanalysis (SEM-EDS), and Uv-Vis spectroscopy. Computational models based on Density Functional Theory (DFT) were used to simulate the structures and properties of some of the perovskites synthesized in this study, in order to validate the experimentally obtained data. The Cs3Bi2I6Br3 perovskite was subjected to modification through A-site doping with K and Rb and X-site doping with Br, with a comprehensive study on the effects of processing variables, anti-solvent quantity, and crystallization temperature using a 23 experimental design. The outcomes highlighted the critical role of the anti-solvent quantity in structure formation and electronic properties. Toluene, as an anti-solvent, produced unique morphologies not commonly reported. Computational studies were performed using Density Functional Theory (DFT) to complement the experimental findings. The optimization process revealed that Cs3Bi2I9 structures mainly constituted [CsI12] and [BrI6] clusters, with Cs–I and Bi–I average bond lengths consistent with experimental results. X-site Br doping induced slight distortion, while A-site Rb/K doping showed minimal lattice parameter changes. Notably, K-induced morphological alterations suggested potential electronic transformations. From an electronic structure perspective, Cs3Bi2I9 had a band gap of 2.07 eV, slightly increased to 2.10 eV with Br doping. Rb maintained Br-doped structure, while K significantly reduced the band gap to 1.96 eV. These computational results align well with our experimental data, showcasing the accuracy of our calculations in predicting material properties. The results confirmed that the perovskites selected through experimental design and validated by computational simulation are promising semiconductor materials for photovoltaic applications, as well as being a lead-free photoabsorbing material option.
Keywords: Bismuth; DFT; Lead-free perovskites; Potassium; Spin coating